Gastronomy as a Cultural Agency: Identity Negotiation and Postcolonial Hybridity in Urban Cuisine - Dwi Febri Syawaludin (Return : Study of Management, Economic and Bussines, 2025)
This study discusses gastronomy as a cultural agency in the context of identity negotiation and postcolonial hybridity in the urban culinary space. The background of the research departs from the fact that culinary is not only a practice of consumption, but also an arena of representation, resistance, and reconstruction of cultural identity. Using a qualitative approach, this research involves observation, in-depth interviews, and document analysis of culinary practices in multicultural cities. The results show that gastronomy functions as a medium of identity articulation through the reinterpretation of colonial heritage, the preservation of traditions, and hybridity innovations. The implications of this study show the importance of urban cuisine in cultural diplomacy, tourism development, and the strengthening of the creative industry, as well as opening up space for critical reflection on colonial memory and globalization.